2019
DOI: 10.3989/gya.0705182
|View full text |Cite
|
Sign up to set email alerts
|

Chia seed oil as an additive to yogurt

Abstract: The aim of this study was to evaluate the effect of a 2% chia seed oil addition to natural yogurt on its quality and to determine whether chia seed oil can be used as an additive in fermented milk products. The dominant species of microorganisms found in yogurt was Lb. delbruecki subsp. bulgaricus. The number in natural yogurt varied from 6.2 to 6.3·106 CFU·g-1 and in enriched yogurt between 6.1 and 6.3·106 CFU·g-1. Chia seed oil contained 4.5 g of sterol per 100 g of oil. The addition of 2% chia seed oil to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
2
0
4
Order By: Relevance
“…None of the studies reported the comparative examination of the fatty acid composition of fermented mare's milk with chia. Results obtained by Derewiaka et al (2019) shows that the addition of 2% chia seed oil to natural yogurt resulted in higher amounts of linoleic and α-linolenic acid. In another study carried out by Eker and Karakaya (2020) the addition of chia seeds caused the detection of α-linolenic and linoleic acids in yogurt containing chia seeds.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies reported the comparative examination of the fatty acid composition of fermented mare's milk with chia. Results obtained by Derewiaka et al (2019) shows that the addition of 2% chia seed oil to natural yogurt resulted in higher amounts of linoleic and α-linolenic acid. In another study carried out by Eker and Karakaya (2020) the addition of chia seeds caused the detection of α-linolenic and linoleic acids in yogurt containing chia seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Семена чиа (Salvia hispanica L.) представляют особый интерес как важный нутрицевтический продукт и богатейший источник пищевых волокон, белков и полиненасыщенных жирных кислот растительного происхождения, в том числе для обогащения продуктов питания функционального назначения и производства продуктов, свободных от глютена [1][2][3]. В масле семян чиа содержится около 60% альфа-линоленовой кислоты (омега-3 жирная кислота), содержание белка в семенах составляет около 20% и пищевых волокон около 30% общего веса [2].…”
Section: Introductionunclassified
“…Важно отметить, что семена чиа не оказывают таких нежелательных эффектов, как аллергические реакции при потреблении в пищу, что позволяет широко использовать их при производстве продуктов питания, в основном в хлебо-булочной и кондитерской промышленности, при производстве паст, каш, йогуртов, десертов и снеков [1,3].…”
Section: Introductionunclassified
See 2 more Smart Citations